PENGARUH TENAGA KERJA BERIJAZAH SMA, PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DAN AKSES PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN GENDER DI INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM PERIODE 2014-2023 - Saputri, Rezza Novitalia; Hayati, Mardhiyah; Taufiqurrahman, Taufiqurrahman (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The Gender Development Index (GDI) in Indonesia is very important to measure the extent to which gender equality is achieved in various sectors, such as education, health, and economy. By monitoring the GDI, the government can design more effective policies to reduce gender inequality and improve the welfare of society as a whole. This study aimed to determine the effect of High School Graduated Workers, Government Expenditure in the Education Sector and Access to Education on the Gender Development Index in Indonesia in the Perspective of Islamic Economics for the period 2014-2023. This study used a Causal study type of research with a qualitative approach, data sources derived from secondary data, panel data obtained are analyzed using multiple linear regression analysis through SPSS Software Version 26. Based on the results of the analysis, it can be concluded that the variables of High School Graduated Workers and Government Expenditure in the Education Sector do not affect the Gender Development Index in Indonesia, with a sig value> 0.05, while Access to Education affects the Gender Development Index in Indonesia with a Sig value of 0.000. The Adjusted R-Square value of 0.420 indicates that the variables of High School Graduated Workers, Government Expenditure in the Education Sector and Access to Education only have an influence of 42% and the remaining 58% is influenced by other variables that were not examined.